Quantum-Powered Entrepreneurial Readiness: Merging Motivation, Technology, and Sustainability (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study introduces and empirically validates a novel model of Quantum-Driven Sustainable Entrepreneurial Readiness (QDSER), integrating psychological and technological dimensions within the framework of Self-Determination Theory (SDT). The model emphasizes the role of intrinsic motivation and technology characteristics in shaping entrepreneurial readiness in the context of quantum-era digital transformation. Data were collected from 142 undergraduate students enrolled in digital business programs and actively engaged in entrepreneurial activities. Using purposive sampling, the study employed Partial Least Squares–Structural Equation Modeling (PLS-SEM) to analyze the relationships among key constructs. Findings reveal that Quantum Machine Learning (QML) significantly enhances both intrinsic motivation and QDSER. Intrinsic motivation—characterized by personal fulfillment, curiosity, and cognitive stimulation—emerges as a strong predictor of entrepreneurial readiness, underscoring its critical role in fostering sustainable engagement with advanced technologies. While technology characteristics also positively influence readiness, their direct impact on intrinsic motivation is comparatively weaker, suggesting that psychological drivers are more central to sustained entrepreneurial behavior in disruptive environments. The study contributes to the digital entrepreneurship literature by conceptualizing QDSER as a multidimensional construct that reflects readiness in the face of quantum technological shifts. It highlights the synergistic interaction between motivational factors and technological affordances, offering a nuanced understanding of how future entrepreneurs can be prepared for rapid innovation cycles. Practical implications are offered for educators, policymakers, and innovation leaders seeking to cultivate quantum-literate, intrinsically motivated entrepreneurial talent. The proposed model serves as a strategic framework for curriculum design, entrepreneurial training, and technology adoption initiatives in higher education and startup ecosystems. By bridging psychological theory with emerging technological paradigms, this research provides a forward-looking perspective on entrepreneurial readiness, positioning QDSER as a foundational construct for navigating the complexities of the quantum economy.